Distributed Task Management by Means of Workflow Atoms - García, Federico (2000)
In this paper we describe Wf-ATOMS, a framework for the specification and management of workflows, whose engine is integrated in a multi user and distributed task management system. The process models include features standard in other workflow management systems, concerning the form in which the activities forming the processes interact, and other features usually managed by user-task management systems that model the different activities available in interactive applications. The conjunction of these two models provides several benefits. On one hand, there is a simplification in the development of workflow-based applications. On the other hand, it allows the systematic development of training applications for work teams that collaborate in the accomplishment of distributed processes. In this paper we describe both the framework from the point of view of the specification of distributed processes and the underlying architecture of the process management system. Wf-ATOMS has been developed as an extension of ATOMS, a previous framework for the management of user tasks in interactive applications.